Residual radiological opacities correlate with disease outcomes in ICU-treated COVID-19 - Björnson, Mikael; Svensson, Ann Mari; He, Cecilia; Sköld, Magnus; Nyrén, Sven; Nygren-Bonnier, Malin; Bruchfeld, Judith; Runold, Michael; Jalde, Francesca Campoccia; Kistner, Anna (Frontiers in Medicine, 2024)
Background: Few studies consider both radiological and functional outcomes in COVID-19 survivors treated in the ICU. We investigated clinical findings and pulmonary abnormalities on chest computed tomography (CT) and compared outcomes of severe versus mild-moderate ARDS on long-term follow-up. Methods: This longitudinal cohort study included 118 COVID-19 patients (median age, 58 years; 79% men). Thoracic CT scans were performed 4, 10 and 22 months after hospital discharge. Two independent blinded radiologists analyzed the 10-month scans and scored the radiology findings semi-quantitatively, as no/minor versus widespread opacities [(low-radiology opacity grade (ROG) versus high-ROG]. ARDS severity was based on the PaO2/FiO2 ratio. Six-minute walk test (6MWT) was performed after 3–and 9–months, lung diffusion capacity for carbon monoxide (DLCO) and lung volume measurement after 9 –and 15–months. Dynamic spirometry was done at all time points. Residual symptoms and health-related quality-of-life (HRQL) were evaluated using validated questionnaires. Results: At 10 months, most patients (81/118; 69%) were classified as high-ROG, of which 70% had severe ARDS during hospitalisation. 69% of those with mild-moderate ARDS also had high-ROG. Patients with high-ROG had longer ICU stay and lower PaO2/FiO2 during hospitalisation (p<0.01). At 9-month follow-up, patients with high-ROG had smaller lung volumes, as % of predicted [(mean (±CI): 80 (77-84) vs 93 (88-98) (p<0.001)], lower DLCO as % of predicted [(74 (70–78) vs 87 (82–92) (p<0.001)], lower oxygen saturation during 6MWT (p=0.02), and a tendency to more severe dyspnoea (p=0.07), but no difference in HRQL compared with no/minor ROG (p=0.92). Higher opacity score was related to lower DLCO at follow-up (r=– 0.48, p<0.001, Spearman rank test). Severe ARDS patients had slightly more severe fatigue at 9-month compared to mild-moderate, but no differences in dyspnoea or lung function at follow-up. Fibrotic-like changes were found in 93% of patients examined with CT scans at 2 years (55/118; 47%). Severe ARDS could predict widespread opacities (ROG>25%) in most patients at follow up at 10-month (AUC 0,74). Conclusions: Residual radiological abnormalities in ICU-treated COVID-19 patients, evaluated up to two years, relate to persisting symptoms and impaired lung function, demanding careful follow-up regardless of ARDS severity at hospitalization.